Influence of Speed and Load on Meshing Impact of Spiral Bevel Gear - Zhai Xiangyi; Yang Jianjun; Hu Xinfang; Zhang Hua (Jixie chuandong)
In order to improve the smoothness of the transmission process of spiral bevel gears, the influence of speed and load on meshing impact in the transmission process is clarified. Firstly, the mathematic model of meshing impact of spiral bevel gear is established, and the force analysis of driven wheel is carried out. Then, the multi-body dynamics model of spiral bevel gear transmission system is established by using Adams software, and the variation law of meshing force and angular acceleration of driven wheel in the transmission process under different rotational speeds and loads is analyzed. If the load is fixed, the increase of the speed will aggravate the meshing impact between the teeth, if the speed is constant, the intensity of meshing impact between the teeth can be reduced and the stability of transmission can be improved by properly increasing the load. It has certain theoretical significance for vibration reduction and noise reduction of spiral bevel gear transmission system.